Performance Analysis and Public Services to Support Sailing Safety and Prevent Sea Traffic Accidents in the Shipping Lanes of L. Say Maumere Port: (Studies in KSOP Class IV Maumere) - Minarto Dian; Fransisko Memo Tukan; Andar Sri Sumantri (Lembaga Penelitian dan Pengabdian kepada Masyarkat-Universitas Terbuka, 2023)
This study aims to determine the analysis of Performance, Public Service and Accident Prevention on Shipping Safety at the L. Say Maumere Port shipping lane. This research was conducted at the Class IV Maumere Harbormaster and Port Authority Office with Shipping Company Agents located at the Port of L. Say Maumere as the population. Data was collected through the methods of Observation, Literature Study, Interviews, Documentation and Questionnaires. The analytical technique used is based on the results of research and multiple analysis with the help of the SPSS V.26 program. Based on the results of research and multiple analysis, the following equation is obtained: Y = 0.106 + 0.376 X1, + 0.357 X2 + 0.256 X3 + . From the multiple linear regression equation, it can be seen that the most dominant variable that influences shipping safety is the performance variable (X1) with a regression coefficient of 0.376. With a coefficient of determination (Adjusted R²) of 0.730 or 73%, which means that the safety of shipping on the shipping lane of L. Say Maumere Port is influenced by the variables of Performance, Public Service, and Accident Prevention, which is 73% and other factors that affect Shipping Safety on the shipping lane. port of L. Say Maumere is 27%. Thus the results of the study indicate that Performance, Public Service, and Accident Prevention have a positive and significant impact on Shipping Safety at the L. Say Maumere Port shipping lane